EVALUASI KINERJA TERMINAL TIPE B SUNGAI KUNJANG KOTA SAMARINDA - WIJAYA, HARIYADI (KURVA S JURNAL MAHASISWA, 2014)
River Terminal Kunjang in Samarinda, is one of these terminals to accommodate large buses serving the route Samarinda-Balikpapan and buses currently serving the route Samarinda to several districts in Kutai upstream, such as Kota Bangun, Muara Kaman, Senoni , as well as to the West Kutai like Melak or Cape Isuy. But the condition is still visible inconvenience for users due to the lack of conformity of terminal facilities in accordance with the terms of a terminal. Performance River Terminal Kunjang looks not function properly due to lack of comfort facilities passengers and passengers prefer to not enter the terminal and wait in Jalan Fortunately Suropati for a ride to the bus they choose, this resulted in a delay in this road, because the wait passengers who got on the bus.               Based on the results of the survey and analysis of the performance of the current Samarinda River Terminal, obtained;10,845 m2 land area, river terminal Kunjang samarinda meet the standards of the land area.±1. The location and footprint Kunjang River Terminal is located at coordinates 0 ° 31'45.82 "S and 117 ° 6'37.97" E, located at the intersection Fortunately Suropati and Jalan Teuku Umar districts ulu Samarinda, Samarinda. Based on the evaluation of terminal land requirements in the initial conditions (existing) in Samarinda Kunjang River terminal can know that the unused land area is now 3,380 m2 while the total land area of 14 152 m2, there are still remaining land area of 10 772 m2 terminal, then by Decree No. 31 of 1995 on road transport terminal at the passenger terminal of type B               The need for parking can be seen from the parking Index (IP), then the performance of the river terminal capacity Kunjang obtained sNilai parking Index (IP) can be seen that if the IP is greater than 100% (IP <100%) means the use of the parking area exceeds the available capacity , Parking at the bus terminal Kunjang River on average 42.29% <100%, then the parking pattern 90o while still meeting the needs of bus parking. Parking River Terminal Kunjang public transportation in an average of 24.43% <100%, then the pattern 90o parking parking while still meeting the needs of public transportation. Four wheels in the parking Kunjang River Terminal average of 3.28% <100%, then the pattern 90o parking parking while still meeting the needs four wheels.